2020
DOI: 10.1007/s10854-020-04251-4
|View full text |Cite
|
Sign up to set email alerts
|

Naturally derived FeTiO3 nanoparticles: analysis of optical properties

Abstract: Eco-friendly metal titanates, which are abundant in nature, are widely used in our day-to-life in a variety of areas. This work is focused on the optical properties of FeTiO 3 (FT) nanoparticles prepared by acid extraction method from ilmenite sand. The prepared FeTiO 3 nanoparticles were analyzed by ultraviolet (UV) spectroscopy. Various linear optical parameters such as refractive index, extinction coefficient, absorption coefficient, real and imaginary parts of dielectric constant, loss tangent, optical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, seawater, mineral wells, ore deposits, and particulate represent potential reservoirs of silver (Ag), gold (Au), carbon (C), and sulfur (S) nanoparticles [39][40][41][42]. Some recent research performed by different researchers has shown how these natural renewable sources can be effectively utilized to produce different nanoparticles, such as metal titanates (FeTiO 3 ) from ilmenite sand, alumina (Al 2 O 3 ) nanoparticles from bauxite, TiO 2 nanoparticles from natural ilmenite, and iron oxide nanoparticles (Fe 3 O 4 ) from ironstone [43][44][45][46]. Iron oxide nanoparticles obtained from ironstone have been found to be in the order of 10 to 50 nm in size when obtained by a simple precipitation method using hydrochloric acid and an ammonia solution [43].…”
Section: Potential Renewable and Sustainable Raw Sources For Differen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, seawater, mineral wells, ore deposits, and particulate represent potential reservoirs of silver (Ag), gold (Au), carbon (C), and sulfur (S) nanoparticles [39][40][41][42]. Some recent research performed by different researchers has shown how these natural renewable sources can be effectively utilized to produce different nanoparticles, such as metal titanates (FeTiO 3 ) from ilmenite sand, alumina (Al 2 O 3 ) nanoparticles from bauxite, TiO 2 nanoparticles from natural ilmenite, and iron oxide nanoparticles (Fe 3 O 4 ) from ironstone [43][44][45][46]. Iron oxide nanoparticles obtained from ironstone have been found to be in the order of 10 to 50 nm in size when obtained by a simple precipitation method using hydrochloric acid and an ammonia solution [43].…”
Section: Potential Renewable and Sustainable Raw Sources For Differen...mentioning
confidence: 99%
“…The obtained precipitate was calcined at 500 • C to obtain spherical particles that were of the order of 50 nm in size on average [45]. FeTiO 3 nanoparticles (or metal titanates in general) can be synthesized by acid extraction followed by a precipitation method, and the resulting nanoparticles have been found to have a size between 50 to 100 nm [46]. It must be mentioned here that although these sources feature abundant amounts of minerals or mineral residues, the chemicals used in the extraction processes are harmful and are certainly not eco-friendly.…”
Section: Potential Renewable and Sustainable Raw Sources For Differen...mentioning
confidence: 99%